2021
DOI: 10.1128/spectrum.01420-21
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Genomic Analysis of Stenotrophomonas maltophilia Strain W18 Reveals Its Adaptative Genomic Features for Degrading Polycyclic Aromatic Hydrocarbons

Abstract: This study provided the latest comparative genomic analysis on Stenotrophomonas maltophilia strains and focused on analyzing their genomic features that allow them to adapt to natural environments. In this study, we set S. maltophilia W18 as a typical PAH-degrading strain of this species. By discussing the genomic adaptative features of degrading PAH, we can predict genomic adaptative features of other S. maltophilia PAH-degrading strains … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 50 publications
2
9
0
Order By: Relevance
“…Combined with previous analyses of the evolutionary relationships of related S. maltobacteria, it could be inferred that isolates from the semblable environmental resources were clustered together, while this conclusion did not apply to clinical isolates due to the differences in the hosts themselves. Our result was consistent with the investigation of S. maltophilia by Yaqian Xiao et al and the genomic analysis of Aeromonas veronii by Hai-chao Song et al (Song et al 2021;Xiao et al 2021), suggesting that there was no evolutionary correlation between the genome and its ecological niche adaptation.…”
Section: Evolutionary Analysis Of S Maltophiliasupporting
confidence: 93%
See 1 more Smart Citation
“…Combined with previous analyses of the evolutionary relationships of related S. maltobacteria, it could be inferred that isolates from the semblable environmental resources were clustered together, while this conclusion did not apply to clinical isolates due to the differences in the hosts themselves. Our result was consistent with the investigation of S. maltophilia by Yaqian Xiao et al and the genomic analysis of Aeromonas veronii by Hai-chao Song et al (Song et al 2021;Xiao et al 2021), suggesting that there was no evolutionary correlation between the genome and its ecological niche adaptation.…”
Section: Evolutionary Analysis Of S Maltophiliasupporting
confidence: 93%
“…Some S. maltophilia isolates were reported to being capable of degrading alkanes, aromatics, and heavy metals, which play an important role in the degradation of pollutants and environmental remediation (Xiong et al 2020) (Venkidusamy and Megharaj 2016) (Jauhari et al 2014). For example, S. maltophilia strain W18 was isolated from crude oil-contaminated soil as a typical PAH-degrading strain of this species (Xiao et al 2021). As for isolates from clinical sources, the transfer of antibiotic resistance genes (ARGs) and virulence factors (VFs) has been reported to occur frequently in recent literatures (Cruz-Cordova et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Our phylogenetic tree was also able to recapitulate most of the established genetic clusters, despite the fact that previous work relied primarily on in silico MLST [17]. Other papers have previously established core genomes of S. maltophilia either by individual gene or by orthogroup [43][44][45][46]. Xu et al established a core genome of 1612 genes at a stricter cutoff of 100 % with only 42 strains, as opposed to the more lenient 80 % cutoff that we used to achieve a similarly sized core genome with 372 strains.…”
Section: Discussionmentioning
confidence: 73%
“…Other papers have previously established core genomes of S. maltophilia either by individual gene or by orthogroup [43–46]. Xu et al .…”
Section: Discussionmentioning
confidence: 99%
“…An analysis of the principal components of the entire study area without dividing it into zones showed that the frequency of the detection of strains capable of only aerobic degradation of hydrocarbons and the presence of the gene for the anaerobic destruction of linear hydrocarbons, masD , are most closely related to the area where gas hydrates were found ( Figure 8 ). In addition, this analysis made revealed a strong relationship between the detection of pmoA and alkBB genes, which can be explained by the fact that in areas of fluid discharge in gas fields, methane is often accompanied by heavier linear hydrocarbons [ 17 , 41 ]. In addition, the detection of the bssA gene was correlated with an increase in the intensity of the anaerobic oxidation of hydrocarbons ( Figure 9 ).…”
Section: Discussionmentioning
confidence: 99%